Optimalisasi Pemasaran Properti Lintas Budaya Melalui Integrated Marketing Communication (IMC) Dan Pelatihan Kompetensi Tim Sales Central Group - Fikra Terisha Azzikra (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to optimize cross-cultural property marketing through the implementation of Integrated Marketing Communication (IMC) and competency training for the sales team at Central Group, one of the leading property developers in Batam. The main challenges faced by the company are the lack of cross-cultural communication skills in the sales team and a marketing strategy that is not yet fully integrated. Therefore, this program is designed to increase marketing effectiveness while strengthening brand image in the multicultural market. This research uses a descriptive-analytical method by collecting data through observation, interviews and documentation analysis. Research stages include planning, implementing training, implementing IMC strategies, monitoring and evaluation. The IMC strategy is implemented through various channels, including social media, paid advertising, traditional media, as well as organizing events such as the Central Property Festival. The research results show significant improvements in marketing strategy coordination, sales team skills, and synergy between the company and the local community. Apart from that, the implementation of IMC has been proven to be able to increase company brand awareness and support the growth of property sales in domestic and international markets. This research makes a practical and academic contribution by offering an integrated marketing strategy model that can be replicated in other property industry contexts.